Antonyms in Trubar's Katehizem z dvejma izlagama (1575) - Orel, Irena (Slavia Centralis, 2020)
The paper will illustrate the systematic and textual use of antonymy in Trubar’s most polemical text, Catehismus s dveima islagama (Catechism with Two Interpretations) which emphasises the duality of interpretation in its very title, while the religious dichotomy is also expressed in the Pridiga od stare prave inu krive vere (Sermon on the Old, True Faith and the False Faith) which will be analysed in more detail.
Keywords: the history of the Slovene standard language; 16th century; Primož Trubar; historical semantics; antonymy